Perancangan Foto Produk di Toko Dee’s Kitchen untuk Meningkatkan Brand awareness - Reza Nurfadhli (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
In today's digital era, photography has been widely applied in various industrial fields and plays a crucial role in attracting consumer attention. Photography has evolved into several disciplines, including landscape photography, wedding photography, street photography, photojournalism, and product photography. Product photography is a high-quality photograph taken to showcase and explain the characteristics and details of a product or service. It not only serves as a representation of the product being offered but also serves as an effective marketing strategy. This applies to the culinary industry, particularly in cakes and food products, where product photography is essential to attract consumers' attention and enhance brand identity. In the case of Dee's Kitchen, the business owner believes that providing good store reviews and creating a positive image for the brand require the influence of influencers. According to an interview with the owner, there is a recognition that their current social media presence on Instagram could be enhanced to reach more potential customers. Therefore, there is a need for Dee's Kitchen to develop its Instagram profile further, making it more diverse and innovative in showcasing its products. This can be achieved by using visually appealing product photos, collaborating with influencers, and engaging with a broader audience through creative marketing strategies. Strengthening the online presence through well-curated photography and social media engagement could help Dee's Kitchen attract new customers, build brand loyalty, and ultimately boost business growth.